Using TRIZ to generate ideas to solve the problem of the shortage of ICT workers - Ang, Mei Choo; Ng, Kok Weng; Ahmad, Siti Azfanizam; Abdul Wahab, Amelia Natasya (Trans Tech Publications, 2014)
With the ever competitive global market swamped with more choices of high-tech gadgets from smartphones to head-mounted display eyewear like "Google Glass", Information and Communication Technology (ICT) is one of the key factors to engineering and technological advancement and the bridge to the future. In view of such significant importance, the government of Malaysia has been embarking on national policies to prioritise the education and the programmes on ICT to train and produce highly skilled ICT workers to achieve the nation's ambition to become a developed country. Despite the government efforts, studies have shown that Malaysia is still currently facing shortage of skilled ICT workers. In view of this shortage of skilled ICT worker problem, a systematic engineering problem solving theory known as TRIZ is applied to generate ideas and potential solutions to solve this problem in this research.